2022
DOI: 10.1111/apt.17251
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: microbial manipulation as therapy for primary sclerosing cholangitis

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…As supported by the cases described in Damman et al’s [ 15 ] review article, our patient’s clinical improvement may be phenomenologically congruent with a direct response to vancomycin’s effect in AIH-PSC. Oral vancomycin has been assessed as a possible treatment for PSC and has been shown to be well-tolerated and linked to improved liver chemistries [ 3 , 17 ]. A large sample-size, randomized, placebo-controlled trial is needed to determine the effect on objective clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…As supported by the cases described in Damman et al’s [ 15 ] review article, our patient’s clinical improvement may be phenomenologically congruent with a direct response to vancomycin’s effect in AIH-PSC. Oral vancomycin has been assessed as a possible treatment for PSC and has been shown to be well-tolerated and linked to improved liver chemistries [ 3 , 17 ]. A large sample-size, randomized, placebo-controlled trial is needed to determine the effect on objective clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…1 Emerging evidence suggests that treatments that target the gastrointestinal microbiome potentially alter the progression of liver disease and improve colitis. 2,3 The large, retrospective, matched cohort study by Ricciuto et al 4 showed that patients of the Paediatric PSC Consortium treated with oral vancomycin -as compared with those receiving conventional therapies but not vancomycin -were almost three times more likely to attain endoscopic remission and had more than triple the odds of achieving clinical remission based on Physician's Global Assessment Score. These findings are aligned with case series [5][6][7] showed that long-term oral vancomycin is associated with induction and maintenance of clinical, endoscopic and histologic remission of colitis in most patients with PSC-IBD, including those who had failed conventional therapies.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
“…In addition, the inflammatory bowel disease (IBD) found in approximately 80% of patients with PSC has a unique phenotype with a high risk of developing poorly controlled IBD or colorectal cancer necessitating colectomy 1 . Emerging evidence suggests that treatments that target the gastrointestinal microbiome potentially alter the progression of liver disease and improve colitis 2,3 …”
mentioning
confidence: 99%
“…However, there is increasing recognition of the gut microbiota in PSC, both as a key player in the pathogenesis, as well as a target of therapy. 1 Ricciuto et al have shed light on the potential for antibiotic therapy to ameliorate colitis evident in up to 80% of patients with PSC and concurrent inflammatory bowel disease (IBD). 2 This large retrospective multi-centre cohort study included 113 patients from the Paediatric PSC Consortium.…”
mentioning
confidence: 99%
“…8 Consequently, other therapies for microbial manipulation have been investigated in PSC, including dietary therapy, probiotics and faecal microbiota transplantation (FMT). 1 FMT is an alternative approach for microbial manipulation in PSC-IBD. It has been shown to be safe and has demonstrated signals for efficacy in terms of improving liver disease.…”
mentioning
confidence: 99%